Mucosal immunity and vaccination strategies: current insights and future perspectives - Zhihao Zhang; Weiqi Hong; Yu Zhang; Xin Li; Haiying Que; Xiawei Wei (Molecular Biomedicine)
Abstract The mucosal immune system represents a critical defense mechanism, safeguarding the body from an array of external pathogens. As the body’s first line of immune protection, it plays an essential role in initiating both innate and adaptive immune responses. Through intricate networks of immune cells and complex molecular pathways, mucosal immunity orchestrates a robust defense not only at the local level but also activates systemic immune responses to ensure comprehensive protection. Consequently, the mucosal immune system has garnered immense interest in the field of vaccine development, given its potential to foster durable and effective immunization. Despite the profound promise of mucosal immunity, the development of mucosal vaccines faces significant challenges, particularly with existing technological platforms that primarily rely on live attenuated or inactivated vaccines. However, emerging innovative platforms, including subunit vaccines, viral vector vaccines, and the groundbreaking application of mRNA vaccines, are offering new perspectives, vastly improving the scope and efficacy of mucosal immunization. As mucosal immunity research continues to evolve, rapid advancements in biotechnology and immunology provide promising strategies to enhance immune responses and overcome inherent limitations. This review delves into the latest progress in oral, nasal, and other forms of mucosal vaccines, analyzing the intricate relationship between mucosal immune characteristics and vaccine design. Emphasis is placed on the pivotal role of advanced adjuvants and delivery systems in maximizing vaccine efficacy. This review addresses current challenges, highlights future research opportunities, and aims to provide a comprehensive framework for advancing the field of mucosal immunity and vaccine development.